Resilient onions: Adapting onion cultivation to climate change - Rahmawan, Hatika; Arista, Nor Isnaeni Dwi; Awanis, Sabila; Deli, Syekh Zulfadli Arofah (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Global climate change poses serious challenges to shallot cultivation. Rising temperatures, altered rainfall patterns, and reduced soil moisture directly affect plant growth and yield, even leading to crop failure due to flooding or drought. To address these issues, adaptive cultivation strategies are needed, including the use of true shallot seed (TSS), efficient irrigation management, and proper fertilization. This study aims to examine the physiological responses of shallot plants to drought stress caused by climate change, assess the effectiveness of TSS technology as an adaptive planting material, and evaluate irrigation and nutrient management practices to support sustainable cultivation. Methods: This study uses a literature review method to synthesize current knowledge on enhancing the resilience of shallot plants to climate variability. Data collection was carried out through a systematic search in scientific databases such as Scopus, Web of Science, PubMed, Google Scholar, and CAB Abstracts, using relevant structured keywords. Data from the selected studies were thematically analyzed to address four main focal points: the physiological and biochemical responses of shallots to drought stress, the development and challenges of adopting True Seed Shallot (TSS) technology, the impact of climate change on nutrient management, and climate-adaptive irrigation management strategies. Findings: Based on the review conducted, climate change, particularly drought stress, has a significant impact on the growth and yield of shallots. Physiological responses such as proline accumulation, soluble sugars, and stomatal closure are key mechanisms in coping with water scarcity, although they also limit plant growth and productivity. The use of True Seed Shallot (TSS) technology has been proven to offer advantages in disease resistance, cost efficiency, and adaptation to changing climatic conditions, although it requires specific cultivation techniques and farmer training. Sustainable agricultural practices, such as drip irrigation, organic fertilization, and the selection of climate-resilient varieties, are essential to enhance crop resilience. Conclusion: integrating drought-resilient practices, such as True Seed Shallot (TSS) technology, efficient irrigation, and nutrient management, is essential to enhance shallot cultivation sustainability under climate change. Novelty/Originality of this article: The novelty of this study lies in its integrated analysis of shallot physiological responses to drought stress, true seed shallot (TSS) technology, and climate-smart irrigation and fertilization practices to enhance shallot resilience under climate change.